Pediatric tuina for allergic rhinitis in children: A systematic review and meta-analysis of randomized controlled trials - Shifang Fu; Yuetong Li; Rongrong Li; Fengjiao Ren; Yinjing Piao; Yanguo Wang; Mingchi Luo (Frontiers Media S.A., 2022)
AimTo evaluate the clinical efficacy of pediatric tuina for allergic rhinitis treatment in children.MethodsThree English, four Chinese, one Japanese, and two Korean databases were searched for relevant literature published till February 2021, and eligible randomized controlled trials (RCTs) were included for analysis. Data were screened and extracted independently using predesigned forms. The methodological quality evaluation was performed using the tool of Cochrane bias risk assessment, and meta-analysis was performed through Review Manager 5.3.ResultsA total of 12 RCTs, which included 716 children, were selected for meta-analysis. Compared with Chinese herbal medicine, acupuncture, Western medicine, and other therapies, pediatric tuina alone or in combination with other treatments had a higher clinical effectiveness (relative risk = 1.16, 95% confidence interval [CI] = 1.08-1.25) in treating children with allergic rhinitis. Pediatric tuina also effectively improved the following signs and symptoms of allergic rhinitis in children: nasal congestion (mean difference [MD] = −0.44, 95% CI = −0.70 to −0.19), runny nose (MD = −0.39, 95% CI = −0.55 to −0.23), sneezing (MD = −0.23, 95% CI = −0.38 to −0.08), and turbinate swelling (MD = −0.26, 95% CI = −0.48 to −0.04); all differences were statistically significant.ConclusionsThe present study provided favorable evidence for the treatment of allergic rhinitis in children with pediatric tuina. However, owing to the impact of research quality, this evidence needs to be validated via strictly designed clinical trials.